Spacer oligonucleotide typing of bacteria of the Mycobacterium tuberculosis complex: recommendations for standardised nomenclature. - Larzábal, Mariano (2010)
Background: Enteropathogenic E. coli (EPEC) and enterohemorrhagic E. coli (EHEC) are two categories of E. coli strains associated with human disease. A major virulence factor of both pathotypes is the expression of a type three secretion system (TTSS), responsible for their ability to adhere to gut mucosa causing a characteristic attaching and effacing lesion (A/ E). The TTSS translocates effector proteins directly into the host cell that subvert mammalian cell biochemistry. Methods/Principal Findings:We examined synthetic peptides designed to inhibit the TTSS. CoilA and CoilB peptides, both representing coiled-coil regions of the translocator protein EspA, and CoilD peptide, corresponding to a coiled-coil region of the needle protein EscF, were effective in inhibiting the TTSS dependent hemolysis of red blood cells by the EPEC E2348/ 69 strain. CoilA and CoilB peptides also reduced the formation of actin pedestals by the same strain in HEp-2 cells and impaired the TTSS-mediated protein translocation into the epithelial cell. Interestingly, CoilA and CoilB were able to block EspA assembly, destabilizing the TTSS and thereby Tir translocation. This blockage of EspA polymerization by CoilA or CoilB peptides, also inhibited the correct delivery of EspB and EspD as detected by immunoblotting. Interestingly, electron microscopy of bacteria incubated with the CoilA peptide showed a reduction of the length of EspA filaments. Conclusions:Our data indicate that coiled-coil peptides can prevent the assembly and thus the functionality of the TTSS apparatus and suggest that these peptides could provide an attractive tool to block EPEC and EHEC pathogenesis.